Social Return on Investment on Fishing Facilities Assistance to the Tegalkamulyan Fisherman Group: A Forecast Analysis - Nonica Hidayati; Abdussalam; Aditya Rahmat Gunawan (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Abstrak Pemberdayaan masyarakat bertujuan untuk meningkatkan kapasitas individu maupun kelompok agar dapat mandiri dalam aspek ekonomi dan sosial. Zakat, Infak, dan Sodakoh (ZIS) menjadi instrumen penting dalam upaya pemberdayaan tersebut. Penelitian ini bertujuan untuk mengukur dampak program bantuan sarana penangkapan ikan yang diberikan oleh Rumah Zakat kepada KUB Mina Sahabat dengan menggunakan pendekatan Social Return on Investment (SROI). Metode yang digunakan dalam penelitian ini adalah metode campuran (kualitatif dan kuantitatif) dengan teknik purposive sampling. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa berdasarkan perhitungan rasio SROI, program ini memperoleh hasil sebesar 1:6. Artinya, setiap Rp1 yang diinvestasikan menghasilkan manfaat sosial sebesar Rp6. Hasil penelitian ini kemudian dapat memperkaya kajian akademik mengenai efektivitas distribusi ZIS dalam pemberdayaan ekonomi berbasis komunitas, serta memberikan panduan bagi lembaga zakat dalam menyalurkan dana secara lebih efektif dan berkelanjutan. Kata kunci: Dampak ZIS, Nelayan, Pemberdayaan Masyarakat, Social Retun on Investment Abstract Community empowerment seeks to enhance the capacity of individuals and groups to achieve economic and social self-sufficiency. Zakat, infaq, and alms (ZIS) serve as key instruments in supporting these empowerment efforts. This study aims to evaluate the impact of the fishing facilities assistance program implemented by Rumah Zakat for the KUB Mina Sahabat group through the Social Return on Investment (SROI) approach. A mixed-methods approach was employed in this study, integrating both qualitative and quantitative methods. The sampling technique used was purposive sampling, and data were collected through a combination of observations, interviews, and documentation analysis. The findings of this study reveal that the SROI ratio is calculated at 1:6. This indicates that for every IDR 1 invested, a social benefit equivalent to IDR 6 is generated. These results contribute to the academic discourse on the effectiveness of ZIS allocation in community-based economic empowerment programs. Furthermore, the findings offer valuable insights for zakat institutions to enhance the effectiveness and sustainability of their fund distribution strategies. Keywords: Impact of ZIS, Fishermen, Community Empowerment, Social Return on Investment